The guidelines for developing integrated marketing communication to promote tourism in Bang Luang Market and Community, Nakhon Pathom Province - Srisawang, Kwanyupa; Buaban, muslin (Journal of Management Science Nakhon Pathom Rajabhat University, 2018)
The research project was to create the guidelines for developing integrated marketing communication to promote tourism in Bang Luang Market and Community, Nakhon Pathom Province. The market and the community are linked because the local people live above their shops. The research was conducted in three steps: identifying the problems; determining the unique attributes of the area; and creating the guidelines. Qualitative and quantitative research was carried out using local participation by in-depth interview, a focus group and questionnaires. The samples were local government groups, local people, entrepreneurs and tourists. The data were analyzed by content analysis, statistical analysis and descriptive method. The results of the research revealed that there were tourism marketing communication problems in Bang Luang Market and Community, specifically the dullness of media, vagueness about the uniqueness and types of tourism, out-of-date information and a lack of media. The research found that the 100- year-old of Bang Luang Market and Community had various tourism resources. The simple lifestyles, traditions and architecture were distinctive and show the cultural combination between Thai and Chinese. This area is suitable for learning about nature or relaxing. There were a variety of local fauna and flora, fresh air and friendly local people. Moreover, the researchers found that the behavior of tourists in this area focused on enjoying local food, relaxing and shopping for local souvenirs. The research team made up of local community members, government representatives and university students decided to rebrand Bang Luang Market and Community tourism with a new image that is suitable to the target tourists: food and festival tourism. After that, they created three kinds of marketing communication; webpage, Fan Page and Posture. These methods were suitable with the new image, timing and budget and were easy to update. In conclusion, the integrated marketing communication to promote tourism will be effective if the local government related to tourism focuses on the target tourists, provides funds and evaluates marketing communication. It is also very important to provide updated information regularly and update of the information is very important too. Moreover, the organization should promote the value of local uniqueness with the local people. Finally, they ought to prepare the officers and community to manage activities for tourists especially learning hands-on activities. Article history : Accepted 16 June 2014 SIMILARITY INDEX = 0.00